High-dose tirofiban pretreatment reduces the need for bail-out study medication in patients with ST-segment elevation myocardial infarction: results of a subgroup analysis of the On-TIME 2 trial. Issue 2 (20th October 2010) - Hermanides, R S; Heestermans, A A C M; ten Berg, J M; Gosselink, A T M; Ottervanger, J P; van Houwelingen, K G; Kolkman, J J E; Stella, P R; Dill, T; Hamm, C; van 't Hof, A W J
Abstract : Objective: This study investigated the outcome of patients who received bail-out study medication and evaluated whether high-dose tirofiban (HDT) pretreatment may reduce the need for bail-out study medication. Design: A prespecified analysis of the multicentre, double-blind, placebo controlled, randomised On-TIME 2 trial. Bail-out use of study medication was predefined and part of the combined clinical end point. Patients: 984 patients excluded from many coronary intervention hospitals in different countries were randomly assigned to HDT or placebo. In the subgroup who received blinded bail-out treatment, patients pretreated with placebo who received bail-out HDT were compared with those pretreated with HDT who received bail-out placebo. Interventions: Routine prehospital initiation of HDT versus bail-out use of HDT. Main Outcome Measures: Electrocardiographic and clinical outcome. Results: Blinded bail-out study medication was used in 24% (237/980) of patients, with a higher rate in patients pretreated with placebo: 29% (140/492) versus 20% (97/488), p=0.002. Bail-out versus no bail-out use of study medication was associated with more residual ST deviation (5.5±7.2 vs 3.7±4.8 mm, p=0.005), and worse clinical outcome (major adverse cardiac events (MACE) at 30 days 12.2% vs 5.6%, p<0.001), mainly due to poor outcome in patients who received HDT bail-out. In patients pretreated with HDT who received placebo bail-out study medication, residual ST deviation and clinical outcome did not differ significantly compared with patients who did not receive bail-out medication (4.0±4.6 vs 3.7± 4.8 mm, p=0.703, MACE 7.2% vs 5.6%, p=0.535). Conclusions: Routine prehospital treatment with HDT significantly reduced the use of blinded bail-out study medication. The need for bail-out therapy was associated with a less favourable outcome. This analysis suggests that routine pretreatment is superior to provisional use of HDT in patients with ST-segment elevation myocardial infarction.